PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN MENGGUNAKAN CAMTASIA BAGI GURU MA’ARIF JEMBER DI ERA PANDEMI - Arifin Nur Budiono; Miftahul Hakim; Benny Afandi (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
The covid-19 outbreak that hit all parts of the world has an impact on all sectors of life, not least the education sector. Therefore, it becomes a challenge for the government, school institutions and educators to strive to be able to organize their education well and safely. One of the policies issued by the government is to organize in an online learning. So that all components of education are required to be able to adapt in the implementation of online learning. One of the skills needed is a learning medium that can support the activity. Therefore, this activity aims to train educators to create learning media using Camtasia software. This devotion is aimed at educators in the LP Ma'arif cabang Jember, especially in subdistrict Wuluhan. The results show that the creation of this video is very useful educators who are expected to have an impact on improving the quality of the video.